Leadership Behaviours as Predictors of an Effective Continuous Improvement Culture in a South African Port Operation - van der Merwe, K.R.; Lourens, A.; Schoeman, N. (The South African Journal of Industrial Engineering, 2025)
The South African port sector faces increasing competitive pressures while remaining vital to the Eastern Cape’s economic and social development. This study investigated how leadership practices influence the creation of a culture that supports continuous improvement (CI), with the aim of developing a causal framework to strengthen CI implementation. By integrating established theories of organisational culture into contemporary insights into CI, the research addressed the cultural barriers that often undermine successful deployment. A literature review confirmed CI as a proven strategy to improve performance in ports, while highlighting cultural misalignment as a key obstacle. Leadership behaviour was identified as central to fostering a CI culture. Using a quantitative methodology, eight leadership dimensions were examined through a structured questionnaire. Reliability and validity were tested, and the results were statistically analysed. The findings revealed significant positive correlations between CI culture and four leadership dimensions: external interaction, process management, organisational values, and supportive leadership. The study recommends refining the framework by specifying the leadership behaviours that are linked to these factors, and extending the research beyond a single South African port.